A Coumarin‐Labeled Vinyl Sulfone as Tripeptidomimetic Activity‐Based Probe for Cysteine Cathepsins. Issue 7 (19th March 2014) - Mertens, Matthias D.; Schmitz, Janina; Horn, Martin; Furtmann, Norbert; Bajorath, Jürgen; Mareš, Michael; Gütschow, Michael
Abstract A coumarin‐tetrahydroquinoline hydride 8 was synthesized as a chemical tool for fluorescent labeling. The rigidified tricyclic coumarin structure was chosen for its suitable fluorescence properties. The connection of 8 with a vinyl sulfone building block was accomplished by convergent synthesis thereby leading to the coumarin‐based, tripeptidomimetic activity‐based probe 10, containing a Gly‐Phe‐Gly motif. Probe 10 was evaluated as inactivator of the therapeutically relevant human cysteine cathepsins S, L, K, and B: it showed particularly strong inactivation of cathepsin S. The detection of recombinant and native cathepsin S was demonstrated by applying 10 to in‐gel fluorescence imaging.